Physiological Roles and Mechanisms of Action of Class I TCP Transcription Factors - Viola, Ivana L.; Alem, Antonela L.; Jure, Rocío M.; Gonzalez, Daniel H. (International journal of molecular sciences, 2023)
TEOSINTE BRANCHED1, CYCLOIDEA, PROLIFERATING CELL FACTOR 1 and 2 (TCP) proteins constitute a plant-specific transcription factors family exerting effects on multiple aspects of plant development, such as germination, embryogenesis, leaf and flower morphogenesis, and pollen development, through the recruitment of other factors and the modulation of different hormonal pathways. They are divided into two main classes, I and II. This review focuses on the function and regulation of class I TCP proteins (TCPs). We describe the role of class I TCPs in cell growth and proliferation and summarize recent progresses in understanding the function of class I TCPs in diverse developmental processes, defense, and abiotic stress responses. In addition, their function in redox signaling and the interplay between class I TCPs and proteins involved in immunity and transcriptional and posttranslational regulation is discussed.